Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

5(2Y - 3) – 4y = 8 – 2y - 15
Justify this please


Sagot :

Answer:

y=1

Step-by-step explanation:

Let's solve your equation step-by-step.

5(2y−3)−4y=8−2y−15

Step 1: Simplify both sides of the equation.

5(2y−3)−4y=8−2y−15

(5)(2y)+(5)(−3)+−4y=8+−2y+−15(Distribute)

10y+−15+−4y=8+−2y+−15

(10y+−4y)+(−15)=(−2y)+(8+−15)(Combine Like Terms)

6y+−15=−2y+−7

6y−15=−2y−7

Step 2: Add 2y to both sides.

6y−15+2y=−2y−7+2y

8y−15=−7

Step 3: Add 15 to both sides.

8y−15+15=−7+15

8y=8

Step 4: Divide both sides by 8.

The value of y is 1

Given the equation 5(2Y - 3) – 4y = 8 – 2y - 15

Expand

10Y - 15– 4y = 8 – 2y - 15

6y - 15 = -7 - 2y

Collect the like terms

6y + 2y = -7 + 15

8y = 8

Divide both sides by 8

8y/8 = 8/8

y = 1

Hence the value y of is 1

Learn more here: https://brainly.com/question/20596193